Sepsis Inflammation Impairs the Generation of Functional Dendritic Cells by Targeting Their Progenitors - Lu, Jie; Sun, Kun; Yang, Huiping; Fan, Dan; Huang, He; Hong, Yi; Wu, Shuiyan; Zhou, HuiTing; Fang, Fang; Li, YanHong; Meng, Lijun; Huang, Jie; et al. (Frontiers in Immunology, 2021)
Background: Sepsis is a complex systemic immune dysfunction syndrome induced by infection. Sepsis has a high mortality rate, with most patients dying due to systemic organ failure or secondary infection. Dendritic cells (DCs) are professional antigen-presenting cells. Upon infection with microbes, DCs are activated to induce adaptive immune responses for controlling infection. DC generation and function are impaired during sepsis; however, the underlying mechanisms remain largely unknown. Method: Peripheral blood samples from sepsis patients were collected to examine DC subsets, DC progenitors, and apoptosis of DCs by flow cytometer. In vitro induction of DCs from hematopoietic stem/progenitor cells were established and a variety of sepsis-associated inflammatory mediators (e.g., interferon-gamma (IFN-γ), interleukin-1beta (IL-1β), tumor necrosis factor-alpha (TNF-α) and granulocyte-colony stimulating factor (G-CSF)) and Lipopolysaccharide (LPS) were determined for the impact on DC generation and function in vitro. Results: Our results demonstrate that sepsis-induced systemic inflammation impairs the capacity of hematopoietic stem and progenitor cells (HSPCs) to produce DCs, including conventional DCs (cDCs) and plasmacytoid DCs (pDCs). We investigated peripheral blood (PB) samples from 34 pediatric patients on days 1 to 7 following diagnosis. Compared to healthy donors (n = 18), the sepsis patients exhibited a significantly fewer percentage and number of pDCs and cDCs, and a lower expression of antigen presenting molecule HLD-DR and co-stimulatory molecules (e.g., CD86) on the surface of DCs. This sepsis-induced DC impairment was associated with significantly increased apoptotic death of DCs and marked decreases of progenitor cells that give rise to DCs. Furthermore, we observed that among the tested sepsis-associated cytokines (e.g., IFN-γ, IL-1β, TNF-α, and G-CSF ), G-CSF and IFN-γ impaired DC development from cultured HSPCs. G-CSF also markedly decreased the expression of HLA-DR on HSPC-derived DCs and their cytokine production, including IL-12 and IFN-β. Conclusions: Collectively, these findings indicate that sepsis impairs the survival of functional DCs and their development from HSPCs. Strategies for improving DC reconstitution following sepsis may restore DC progenitors and their associated function.